Tourism Performance Development Strategy of Fakfak Regency (Empirical Study of the Suitability of Resource Potential and Entrepreneurial Readiness of the Community of Tanama Village, Pariwari District) - Samsudin Rengen; Pompong Budi Setiadi; Christina Wulansari (RTTM, 2024)
The exoticism, nuances and natural beauty are the characteristics of Tanama village, Pariwari district in Fakfak Regency has not been realized and utilized as much as possible by the local community and tourism investors. The purpose of the research is to reveal efforts to prepare a roadmap for the acceleration of tourism development and the creative economy that can be developed by encouraging the improvement of the entrepreneurial performance of the Tanama village community. The research was carried out for 6 months from July to December 2023. Descriptive research method with a combination approach of quantitative analysis. Data was obtained through a direct survey of respondents who had been deliberately determined. The data obtained are given a weight value based on the assessment indicators obtained from the results of the preliminary research. The results of the study are presented in the form of a spider web diagram equipped with illustrations of shift share gap values, Ishikawa diagrams, Pearson correlation analysis, and regression equation models obtained from the SPSS statistical device version 2.3.